2012
DOI: 10.1108/00346651211212024
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of antioxidant activity and phytochemical profile in native plants

Abstract: Purpose -The purpose of this paper is to study the structure-activity correlation of four medicinal plants -Ocimum basilicum L., Piper betle L., Grewia asiatica L., Lantana camara L. in crude methanolic extract. These plants have been used in Ayurvedic preparation as alternative medicine. The contents of phenolic compounds (flavonoids, anthocyanin) and antioxidant capacities were evaluated. Design/methodology/approach -Folin-Ciocalteu method was used for the analysis of the phenolic compounds. Total flavonoids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 15 publications
5
20
0
Order By: Relevance
“…Previously it was reported that the methanolic extract of L. camara's flowers showed to be potentially effective in reducing iron, worth 29.90 mg of gallic acid/g of extract (Srivastava et al, 2012). Bangou et al (2012) reported that the reduction potential of the methanolic extract of L. camara's leaves was 8.17 mM ascorbic acid/g of extract, which is close to that observed for ethanol extract in this work.…”
Section: Frap (Ferric-reducing Antioxidant Power)supporting
confidence: 86%
“…Previously it was reported that the methanolic extract of L. camara's flowers showed to be potentially effective in reducing iron, worth 29.90 mg of gallic acid/g of extract (Srivastava et al, 2012). Bangou et al (2012) reported that the reduction potential of the methanolic extract of L. camara's leaves was 8.17 mM ascorbic acid/g of extract, which is close to that observed for ethanol extract in this work.…”
Section: Frap (Ferric-reducing Antioxidant Power)supporting
confidence: 86%
“…G. asiatica has been cited as a good source of phenolic acids, flavonoids and a small amount of tannins. However, more promising results have been delivered from the present study compared with earlier studies where G. asiatica methanolic extracts were found to deliver 144 mg GAE/g total phenolics, 4.61 mg QE/g total flavonoids and 4.9 mg/kg anthocyanins [33,34].…”
Section: Phytochemical Constituents Of G Asiatica Extractssupporting
confidence: 42%
“…The obtained amount of anthocyanins in LPP was more as compared to fresh phalsa fruit, which attributed to rise in the dry matter content owing to the evaporation of water. Crude methanolic extracts of this fruit showed total phenols 144.11 mg GAE/g and total anthocyanin 4.88 mg/kg Srivastava et al (2012). Kaur and Kapoor (2005) also obtained moderate amounts of total phenols i.e., 55-87 mg/100g in phalsa.…”
Section: Bioactive Compoundsmentioning
confidence: 80%